Sialodocholithiasis - A case report and review - Ashima Bali Behl; Salvina Grewal; Bharti Lamba; Vikram Bali (Wolters Kluwer Medknow Publications, 2020)
A majority of sialoliths occur in the submandibular gland or its duct and are a common cause of acute and chronic infections. This report describes the case of a patient who had an unusual submandibular gland duct sialolith (calculus) that was completely obstructing the submandibular gland duct (sialodocholithiasis) and the use of the computed tomography and ultrasonography as a diagnostic aid and a surgical guide. Patients with sialolithiasis require definitive surgical treatment in most cases, which results in an excellent prognosis. Along with presenting the case report, this article also reviews the etiology, diagnosis, and various treatment modalities available for the management of salivary gland calculi depending on their site and size.